Physiological Limits to Zinc Biofortification of Edible Crops - White, Philip J.; Broadley, Martin R. (Frontiers in Plant Science, 2011)
It has been estimated that almost one third of the world’s population lack sufficient Zn for adequate nutrition. This can be alleviated by increasing dietary Zn intakes through Zn-biofortification of edible crops. Biofortification strategies include the application of Zn-fertilisers or the development of crop genotypes that acquire more Zn from the soil and accumulate it in edible portions. Zinc concentrations in roots, leaves and stems can be increased through the application of Zn-fertilisers. Root Zn concentrations of up to 500-5000 mg kg-1 DM, and leaf Zn concentrations of up to 100-700 mg kg-1 dry matter (DM), can be achieved without loss of yield when Zn-fertilisers are applied to the soil. It is possible that greater Zn concentrations in non-woody shoot tissues can be attained using foliar Zn-fertilisers. By contrast, Zn concentrations in fruits, seeds and tubers are severely limited by low Zn mobility in the phloem and Zn concentrations higher than 30-100 mg kg-1 DM are rarely observed. However, genetically modified plants with improved abilities translocate Zn in the phloem might be used to biofortify these phloem-fed tissues. In addition, genetically modified plants with increased tolerance to high tissue Zn concentrations could be used to increase Zn concentrations in all edible produce and, thereby, increase dietary Zn intakes.